Attitude and the Mediating Role in Online Food Delivery Continuance Intention - Lily Purwianti; Hepy Hefri Ariyanto; Christella (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2025)
Background: The online food delivery (OFD) sector has grown rapidly in Indonesia, necessitating scholarly examination of consumer behavior beyond initial adoption to understand continuance patterns in technology-enabled consumption. Purpose: This research aims to analyze the effects of food safety risk perception, social influence, price savings, and time savings on consumers' continuance intention toward OFD services, with attitude as a mediating variable. Method: A quantitative survey of 384 OFD users in Batam City, Indonesia, who had used the services three times in three months was conducted, and the data were analyzed using PLS-SEM. Findings: Social influence, price savings, time savings, and food safety risk perception significantly affect attitude and continuance intention through the mediation of attitude. Food safety risk exhibits dual effects of direct negative and indirect positive effects through attitude. Conclusions: Attitude serves as a critical mediator consistent with the Theory of Planned Behavior. OFD providers should strengthen food safety assurances, leverage social influence, emphasize efficiency benefits, and enhance positive attitudes to sustain consumer loyalty and long-term engagement. Research implication: OFD service suppliers should strengthen consumer confidence by addressing food safety concerns, leveraging social influence, and emphasizing time and cost efficiency. Marketing and operations also improve positive consumer attitudes to support long-term engagement.